ABOUT THE STRENGTH OF ISOTROPIC MATERIALS WITH SPATIAL STOCHASTIC DISTRIBUTION OF DEFECTS - Квіт, Роман Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The model of a stochastically defective body is considered, the strength study of which is based on the distribution function of failure loading in the form of the Weibull type. The body is under the conditions of a homogeneous axisymmetric loading and has evenly distributed disc-shaped cracks that do not interact with each other. The correlations for finding a number of fracture statistical characteristics are obtained: probability of failure, mean value, dispersion and variation coefficient of failure loading. The influence of applied loading type, the number of defects (body sizes) and material heterogeneity on the specified fracture statistical characteristics have been investigated.